2004
DOI: 10.1002/pdi.572
|View full text |Cite
|
Sign up to set email alerts
|

The Kerraboot®: A novel wound dressing device for the management of leg and foot ulcers

Abstract: Foot and lower leg ulcers are particularly common in patients with diabetes. Current management strategies are often complex and time consuming for health care professionals and uncomfortable for the patient. A novel wound dressing device, the Kerraboot®, was assessed for its ease of use and patient acceptability in 14 patients with foot and lower leg ulcers. The dressing device was used for a period of up to 28 days, after which patients and health care professionals were asked to complete questionnaires. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Previously, Kerraboot ® has been shown to facilitate healing in lower limb (diabetic) ulcers. 2,3 This case study has demonstrated a significant improvement in an extensive wound bed after three weeks of once-daily use, with formation of a healthy granulation tissue base. Complete healing was noted after eight months, thus preventing the need for a second lower limb amputation.…”
Section: Discussionmentioning
confidence: 85%
“…Previously, Kerraboot ® has been shown to facilitate healing in lower limb (diabetic) ulcers. 2,3 This case study has demonstrated a significant improvement in an extensive wound bed after three weeks of once-daily use, with formation of a healthy granulation tissue base. Complete healing was noted after eight months, thus preventing the need for a second lower limb amputation.…”
Section: Discussionmentioning
confidence: 85%
“…In clinical studies1 Kerraboot® has been shown to reduce nursing time required to change the ulcer dressing by an average of 70%. In the case of one individual patient this meant a dressing change time of only 2 minutes with Kerraboot® compared to an estimated average of 30 minutes for standard dressings.…”
Section: Drug Tariff Approval For Home Use Of Kerraboot®mentioning
confidence: 99%